The influence of financial literacy and financial inclusion on financial management at the Roemah Difabel Indonesia foundation - Faradhela Happy Rahmadani; Andi Kartika (Jurnal Pendidikan Ekonomi (JUPE), 2026)
Understanding how financial inclusion and financial literacy affect the Roemah Difabel Indonesia Foundation financial management was the aim of this study. This study employs a quantitative approach using multiple regression analysis. Data collection methods used in this study include observation, surveys, and documentation. The study was conducted at the Roemah Difabel Indonesia Foundation, with a sample size of 51 respondents with various types of disabilities. The findings demonstrated that financial literacy have negative, not significant, and financial inclusion had a positive and significant. Additional research revealed that the Roemah Difabel Indonesia Foundation financial management was significantly impacted by financial inclusion and financial literacy. People with disabilities at the Roemah Difabel Indonesia Foundation are more educated about financial inclusion than financial literacy because, in practice, they can access financial services but lack the knowledge to manage them.